Deficiency of endothelial FGFR1 alleviates hyperoxia-induced bronchopulmonary dysplasia in neonatal mice - Long, Yanrong; Chen, Hongbin; Deng, Junchao; Ning, Junjie; Yang, Pengbo; Qiao, Lina; Cao, Zhongwei (Frontiers in Pharmacology, 2022)
Disrupted neonatal lung angiogenesis and alveologenesis often give rise to bronchopulmonary dysplasia (BPD), the most common chronic lung disease in children. Hyperoxia-induced pulmonary vascular and alveolar damage in premature infants is one of the most common and frequent factors contributing to BPD. The purpose of the present study was to explore the key molecules and the underlying mechanisms in hyperoxia-induced lung injury in neonatal mice and to provide a new strategy for the treatment of BPD. In this work, we reported that hyperoxia decreased the proportion of endothelial cells (ECs) in the lungs of neonatal mice. In hyperoxic lung ECs of neonatal mice, we detected upregulated fibroblast growth factor receptor 1 (FGFR1) expression, accompanied by upregulation of the classic downstream signaling pathway of activated FGFR1, including the ERK/MAPK signaling pathway and PI3K-Akt signaling pathway. Specific deletion of Fgfr1 in the ECs of neonatal mice protected the lungs from hyperoxia-induced lung injury, with improved angiogenesis, alveologenesis and respiratory metrics. Intriguingly, the increased Fgfr1 expression was mainly attributed to aerosol capillary endothelial (aCap) cells rather than general capillary endothelial (gCap) cells. Deletion of endothelial Fgfr1 increased the expression of gCap cell markers but decreased the expression of aCap cell markers. Additionally, inhibition of FGFR1 by an FGFR1 inhibitor improved alveologenesis and respiratory metrics. In summary, this study suggests that in neonatal mice, hyperoxia increases the expression of endothelial FGFR1 in lung ECs and that deficiency of endothelial Fgfr1 can ameliorate hyperoxia-induced BPD. These data suggest that FGFR1 may be a potential therapeutic target for BPD, which will provide a new strategy for the prevention and treatment of BPD.